2022
DOI: 10.1162/nol_a_00054
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Frequency and Sentence Context Influence the Brain’s Response to Single Words

Abstract: Typical adults read remarkably quickly. Such fast reading is facilitated by brain processes that are sensitive to both word frequency and contextual constraints. It is debated as to whether these attributes have additive or interactive effects on language processing in the brain. We investigated this issue by analysing existing magnetoencephalography data from 99 participants reading intact and scrambled sentences. Using a cross-validated model comparison scheme, we found that lexical frequency predicted the w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 96 publications
(228 reference statements)
1
15
0
Order By: Relevance
“…however previous studies have shown that they interact during late stages of word processing (Fruchter et al, 2015;Huizeling et al, 2022). In a naturalistic listening paradigm, even though it is an instrumental way to study language comprehension, it is not fully possible to control for word frequency or to completely dissociate it from any sentence context effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…however previous studies have shown that they interact during late stages of word processing (Fruchter et al, 2015;Huizeling et al, 2022). In a naturalistic listening paradigm, even though it is an instrumental way to study language comprehension, it is not fully possible to control for word frequency or to completely dissociate it from any sentence context effects.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, to disassociate the effects of word entropy and word frequency, we modelled word frequency with an assumption that entropy and frequency have linearly additive effects; however previous studies have shown that they interact during late stages of word processing (Fruchter et al, 2015; Huizeling et al, 2022). In a naturalistic listening paradigm, even though it is an instrumental way to study language comprehension, it is not fully possible to control for word frequency or to completely dissociate it from any sentence context effects.…”
Section: Discussionmentioning
confidence: 99%
“…While Murphy (2019, 2021a) documented the frequency profiles of nominal senses in copredications, the authors declare without evidence that CITY “is connected to child nodes like” government , population, and geography , with a “high conditional probability” being that the “jump” will land on government . The author's model concerns prediction, but what is missing is a discussion of lower‐level statistics pertaining to lexicality, such as frequency, which is known to intimately relate to linguistic predictions and language processing more generally (Huizeling, Arana, Hagoort, & Schoffelen, 2022), and their new apparatus of sense node “jumping” is not anchored around any clear psycholinguistic architecture.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Prior to conducting this study, we did not test whether the children also knew these verbs and whether they had already acquired them or not (as we were mainly interested in whether children were able to interpret our pictures equally well with an active and a passive structure). For this reason, if researchers intend to use our materials to test, for instance, the online processing of transitive structures, it should be noted that lexical frequency may affect sentence processing (Huizeling et al, 2022). We emphasize, however, that the children only provided 7% incorrect answers, which means that we should not overlook the fact that our materials did largely elicit correct interpretations of both active and passive descriptions of transitive events (93%).…”
Section: Limitations and Future Directionsmentioning
confidence: 96%